Huangqin Qingre Chubi Capsule is Associated with Reduced Risk of Readmission in Patients with Rheumatoid Arthritis: A Real-World Retrospective Cohort Study - Hu Y; Liu J; Xin L; Wan L; Qi Y; Li Y; Chen Y (International Journal of General Medicine, 2023)
Yuedi Hu,1,2 Jian Liu,1,3,4 Ling Xin,3,4 Lei Wan,1,3,4 Yajun Qi,1 Yang Li,1 Yiming Chen1 1Department of Rheumatology, The First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui, People’s Republic of China; 2College of Chinese Medicine, Anhui University of Chinese Medicine, Hefei, Anhui, People’s Republic of China; 3Institute of Rheumatology, Anhui University of Chinese Medicine, Hefei, Anhui, People’s Republic of China; 4Department of Internal Medicine Application Foundation Research and Development, Anhui Province—Key Laboratory of Modern Chinese Medicine, Hefei, Anhui, People’s Republic of ChinaCorrespondence: Jian Liu, Department of Rheumatology, The First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui, 230031, People’s Republic of China, Tel +86 13955109537, Email liujianahzy@126.comPurpose: The therapeutic effects of Huangqin Qingre Chubi (HQC) in rheumatoid arthritis (RA) have been documented. However, there is a lack of real-world clinical evidence supporting its efficacy.Methods: Patients diagnosed with RA were recruited from the First Affiliated Hospital of the Anhui University of Chinese Medicine. Patient information was obtained from the hospital’s database. Propensity score matching (PSM), Kaplan–Meier curve, and Cox proportional hazards model were used to control confounding factors and analyze the factors influencing readmission. Association rule analysis and random walk evaluation models were used to evaluate the correlations among HQC treatment, inflammation indicators, and self-perception of patients (SPP) scale.Results: After PSM, 3423 patients were enrolled, with 1142 in the HQC group and 2281 in the non-HQC group. The readmission risk of the HQC group was significantly lower than that of the non-HQC group. Combined univariate and multivariate analysis results revealed that risk factors for readmission were age > 60 years, female sex, hypertension, chronic gastritis, and elevated levels of laboratory indices, including anticyclic citrullinated peptide and complement component 3 (C3) and C4. HQC, disease-modifying antirheumatic drugs, nonsteroidal anti-inflammatory drugs, and glucocorticoid therapy were protective factors for readmission. HQC treatment was closely associated with improvements in many factors, including erythrocyte sedimentation rate, C-reactive protein, C3, rheumatoid factor levels, visual analog scale, depression self-assessment scale, and patient-reported activity index scores with RA.Conclusion: HQC treatment can reduce the risk of readmission and significantly improve immune inflammatory indicators and SPP in patients with RA, with no risk of hepatorenal toxicity.Keywords: Huangqin Qingre Chubi capsule, traditional Chinese medicine, rheumatoid arthritis, readmission